2021
DOI: 10.1177/23259671211053012
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Achieve Threshold Scores on Patient-Reported Outcome Measures Within 1 Year Has a Predictive Risk of Subsequent Hip Surgery Within 5 Years of Primary Hip Arthroscopy: A Case-Control Study

Abstract: Background: Research has identified factors that influence achievement rates of threshold scores on patient-reported outcome measures (PROMs) after hip arthroscopy. However, little data exist on whether failure to achieve a threshold score (minimal clinically important difference [MCID] or substantial clinical benefit [SCB]) in the short term after hip arthroscopy predicts the risk of future hip surgery. Purpose/Hypothesis: The purpose of this study was to determine if failure to achieve the MCID or SCB on PRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…One study showed that patients not meeting the MCID or substantial clinical benefit by 1 year postoperatively are at risk of subsequent surgery within 5 years postoperatively. 20 Furthermore, the trend identified in VAS pain scores can likely be attributed to the timeline of patients undergoing revision and conversion to THA; from 2 to 5 years postoperatively, patients who would undergo secondary surgery were still included in PRO analyses, contributing to the higher VAS pain scores seen at the 5-year time point. When these patients undergoing secondary surgery (revision and conversion to THA) were excluded subsequently beyond the 2- to 5-year time frame, the VAS scores therefore improved at 10 years postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that patients not meeting the MCID or substantial clinical benefit by 1 year postoperatively are at risk of subsequent surgery within 5 years postoperatively. 20 Furthermore, the trend identified in VAS pain scores can likely be attributed to the timeline of patients undergoing revision and conversion to THA; from 2 to 5 years postoperatively, patients who would undergo secondary surgery were still included in PRO analyses, contributing to the higher VAS pain scores seen at the 5-year time point. When these patients undergoing secondary surgery (revision and conversion to THA) were excluded subsequently beyond the 2- to 5-year time frame, the VAS scores therefore improved at 10 years postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…35,39,49 Previously published long-term clinical outcomes assessing the efficacy of hip arthroscopic surgery for the treatment of FAIS have necessarily included patients without capsular repair and/or labral repair when such procedures would be indicated in modern practice. [17][18][19][20][21][22][23][24][25] As a result, these investigations do not reflect the long-term findings associated with contemporary techniques for the treatment of FAIS, including surgical correction of pathomorphology, chondrolabral refixation, and capsular management. The current literature supports that hip arthroscopic surgery for FAIS has reliable short-and midterm patient-reported outcomes (PROs) and clinical success, 2,15,30,38,43,52,57,70 including in athletes 11,12,59 and adolescents, 31,42 among other unique populations.…”
mentioning
confidence: 99%